A first Passover - Swartz, Leslie; Chwast, Jacqueline (New York : Aladdin Paperbacks, 1992)
Encourages awareness and appreciation of Korean American cultures.
Reprint: Originally published: Cleveland : Modern Curriculum Press, c1992.
007-010.
Keywords: Jews -- United States -- Fiction; Jews -- United States -- Social life and customs -- Fiction; Jews -- United States -- Celebration -- Fiction; Multicultural education; Multicultural education; Passover -- Fiction; Jews -- Fiction